1990
DOI: 10.1164/ajrccm/142.5.1026
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function after Heart-Lung Transplantation Using Larger Donor Organs

Abstract: Restrictive pulmonary function after heart-lung transplantation (HLT) has been attributed to the use of smaller donor lungs and/or an inability to generate normal negative pleural pressures. Pleural pressure generation depends on both the size of the recipient thoracic cage and its neuromuscular integrity. To determine whether lung volumes after heart-lung transplantation are more dependent on donor lung size or on recipient chest wall characteristics, seven HLT recipients were evaluated before and after trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Following LT, after initial falls, post-operative values for total lung capacity (TLC) approach the recipient9s predicted value at 1 yr post-transplant, irrespective of the size of the donor lungs, suggesting that characteristics of the chest wall are the major determinants of post-operative lung volume, and not the donor lung size or compliance [61,62]. The stable pulmonary function observed after HLT has been reported to be consistent with a mild restrictive ventilatory pattern [43].…”
Section: Pulmonary Functionmentioning
confidence: 99%
“…Following LT, after initial falls, post-operative values for total lung capacity (TLC) approach the recipient9s predicted value at 1 yr post-transplant, irrespective of the size of the donor lungs, suggesting that characteristics of the chest wall are the major determinants of post-operative lung volume, and not the donor lung size or compliance [61,62]. The stable pulmonary function observed after HLT has been reported to be consistent with a mild restrictive ventilatory pattern [43].…”
Section: Pulmonary Functionmentioning
confidence: 99%
“…RESULTS: The pTLC ratio was available for 70 patients: 31 were undersized and 39 oversized. Undersized patients had a higher LAS (40.4 vs 35.8, p ϭ 0.009), were more often in the intensive care unit (ICU) pre-LTx (35% vs 10%, p ϭ 0.01), and had a higher occurrence of primary graft dysfunction (PGD; 25% vs 5%, p ϭ 0.013) and tracheostomy (32% vs 10%, p ϭ 0.02), longer index hospitalizations (20 [interquartile range (IQR), 10 -46] vs 16 [IQR,[12][13][14][15][16][17][18][19][20][21][22][23][24][25] days, p ϭ 0.048), and higher index hospitalization charges ($176,247 [IQR, $137,012] vs $158,492 [IQR, $136,301], p ϭ 0.04). After adjusting for LAS and pre-LTx ICU stay, a lower pTLC ratio remained associated with higher hospital charges (p ϭ 0.049).…”
mentioning
confidence: 99%
“…1 This phenomenon was also observed by Massard et al' in DLT recipients with cystic fibrosis whose preoperative TLC were below 100% of the predicted normal values. Although several authors have observed that postoperative TLC returned to preoperative measured TLC in heart-lung transplant patients (5,6,8), this was probably because the preoperative TLCs were near normal. These findings suggested that the preoperative abnormal thoracic volume could be neglected, and that the predicted normal TLC should be compared between the donor and the recipient for chest size matching.…”
Section: Discussionmentioning
confidence: 92%
“…Our previous study' has shown that in DLT recipients with emphysema who had received larger donor lungs, the post-transplant VC was not influenced by the size of the donor lung but was more dependent on the recipient' s thoracic volume (5,7,8). The finding in the present study that posttransplant VC was significantly correlated with the predicted normal VC of recipient (r = 0.74, p = 0.002) supported our previous conclusion (Fig.…”
Section: Discussionmentioning
confidence: 99%